Le tecnologie di osservazione della terra e di diagnostica elettromagnetica al servizio dei beni culturali: l’esperienza dell’IREA-CNR - Francesco Soldovieri; Romeo Bernini; Manuela Bonano; Ilaria Catapano; Gianfranco Fornaro; Maria Consiglia Rasulo; Olga Zeni; Riccardo Lanari (Archeomatica, 2016)
IREA (an Institute of the Italian National Research Council) develops methodologies and technologies for acquisition, processing, fusion and interpretation of images and data obtained by using electromagnetic sensors (operating on satellite, aircraft and in situ), aimed at monitoring environment and territory, at non-invasive diagnostic and at electromagnetic risk assessment. These scientific activities have a significant follow-up in the fields of Cultural Heritage (CH) monitoring and protection. IREA is an excellence level Institute with a very solid international visibility, gained thanks to a very good scientific production and through the involvement in national and international projects. IREA is also involved in the organization of scientific events, conferences, summer schools and contributes to the editorial board of several international journals. Awards have been assigned to IREA laboratories and researchers who collaborate with many CH institutions in Italy and abroad.